PENGARUH MODEL DISCOVERY LEARNING TERHADAP KEMAMPUAN PEMECAHAN MASALAH MATEMATIS PESERTA DIDIK KELAS VIII SMPN 1 PADANG PANJANG - Suci Anggelya Sri Rahayu (Jurnal Edukasi dan Penelitian Matematika, 2020)
Mathematics problem solving ability is important in learning process. But in the reality, students mathematical problem solving ability is still low. Effort that can be used are implementing Discovery Learning (DL) model. The purpose of this study is to analyze and describe the mathematical problem solving ability who learn to use DL model is better than the mathematical problem solving ability who learn to use conventional learning. This type of research is quasi experiment with Randomized Control Group Only and descriptive research. The population is student of class VIII SMPN 1 Padang Panjang with sample of class VIII B and VIII C. The instrument used was a test of mathematical problem solving ability. Based on the result , it can be concluded that the mathematical problem solving ability of student who learn with DL model is better than student who learn with conventional learning. Keywords __ Mathematical Problem Solving Ability, Discovery Learning, Saintific Approach, Student Worksheet